2018
DOI: 10.1088/1361-6528/aad3f4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocatalytic oxygen evolution activity by formation of Ir@IrOx(OH)y core–shell heterostructure

Abstract: Developing efficient catalysts to accelerate the rate of oxygen evolution reaction (OER) is critical for photocatalytic water-splitting. In this work, metallic Ir, IrO(OH), and core-shell Ir@IrO(OH) were synthesized and employed as OER catalysts for photocatalytic water oxidation. It was found that the Ir@IrO(OH) core-shell heterostructure catalyst showed the best photocatalytic performance among these three catalysts, with the oxygen evolution rate as high as 59.63 mmol g h. Detailed investigations revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…critical value increases with the decrease of the channel width and the increase of the hydrated ion radius. Many works have been carried out to achieve ion selective separation by changing the surface charge, for example, Zhao et al [184] showed that the negatively charged graphene pores can reject Cl − and improve K + transport, which was consistent with the experimental results of O'hern et al [15] Li et al [139] found that ions cannot pass through 30% strained monolayer graphene when membrane charge density was below 5.67 e nm −2 because of the steric exclusion, and enhanced electrostatic interaction could balance the vdW interaction and lower the energy barrier for the counterion. Once the membrane charge density increases to 6.8 e nm −2 , all the K + will be separated from the mixed solution of K + and Na + .…”
Section: Ion Selectivity Of Modified Nanochannelssupporting
confidence: 65%
See 1 more Smart Citation
“…critical value increases with the decrease of the channel width and the increase of the hydrated ion radius. Many works have been carried out to achieve ion selective separation by changing the surface charge, for example, Zhao et al [184] showed that the negatively charged graphene pores can reject Cl − and improve K + transport, which was consistent with the experimental results of O'hern et al [15] Li et al [139] found that ions cannot pass through 30% strained monolayer graphene when membrane charge density was below 5.67 e nm −2 because of the steric exclusion, and enhanced electrostatic interaction could balance the vdW interaction and lower the energy barrier for the counterion. Once the membrane charge density increases to 6.8 e nm −2 , all the K + will be separated from the mixed solution of K + and Na + .…”
Section: Ion Selectivity Of Modified Nanochannelssupporting
confidence: 65%
“…Simplified view of a double layer of negative ions in the electrode and solvated positive ions in the liquid electrolyte, separated by a layer of polarized solvent molecules. [144] Li et al [139] analyzed the structure of water molecules around the ion and found that the hydration layers were almost peeled on the solid-liquid interface due to the effects of the electrostatic force and the vdW force. For the nanochannel with a constant size, the relation of driving force and molecular aggregation radius can be described by the Stoke's law…”
Section: Ionmentioning
confidence: 99%
“…Water electrolysis to generate hydrogen has received much attention recently . Electrochemical water splitting undergoes an oxygen evolution reaction (OER) at the anode and a hydrogen evolution reaction (HER) at the cathode . Highly active catalysts are regularly demanded to lower the overpotentials and accelerate the reaction rates at the electrode/electrolyte interface .…”
Section: Introductionmentioning
confidence: 99%
“…Highly active catalysts are regularly demanded to lower the overpotentials and accelerate the reaction rates at the electrode/electrolyte interface . The state‐of‐the‐art catalyst for HER is platinum supported on active carbon, and for OER is expensive iridium oxide (IrO 2 ) . Great efforts have been made to find more active, more stable, and inexpensive alternative OER and HER catalysts to replace rare and noble metals/oxides.…”
Section: Introductionmentioning
confidence: 99%
“…The PFC operates in the light and also in the dark as conventional FC with high electrical output power at room temperature. 33,34 In the XPS spectra of InGaN, there are no changes upon the deposition of IrO x (OH) y . Also, there are no changes during the photoelectrochemical oxygen evolution reaction, which has been confirmed before.…”
Section: Introductionmentioning
confidence: 99%